102 Seratus dua English games (from A to Z) : acties, ice breakers, warm ups, creativities, fillers, energizers, quizzes - Agoetyowati, Redjeki (Gramedia Pustaka Utama, 2008)
xiii, 267 p. : il.; 23 cm.